Central obesity and its association with metabolic syndrome in adolescent students of Aceh Sport High School: A cross-sectional study - Nurul Nadia; Herlina Dimiati; Eka Yunita Amna; Rusdi Andid; Nora Sovira; T.M. Thaib (AcTion: Aceh Nutrition Journal, 2025)
Obesity remains a significant nutritional issue in the pediatric population and is closely linked to metabolic disorders. According to the World Health Organization (2022), 160 million individuals aged 5–19 years are classified as obese.  This study aimed to evaluate the association between central obesity and metabolic syndrome (MetS) in sports students. This cross-sectional study was conducted at Aceh Sports High School from May to August 2024, involving 43 students selected through simple random sampling. Although the sample size was relatively small, these findings offer valuable preliminary insights. The data collected included demographics, anthropometric measurements, blood pressure, and blood tests (glucose, HDL cholesterol, and triglycerides). Central obesity was assessed using waist circumference and MS was evaluated based on the NCEP ATP III criteria. Data were analyzed descriptively, followed by the chi-square test. The majority of the participants were not at risk of MS (51,2%). However, chi-square analysis revealed a statistically significant association between waist circumference and MetS (p<0,001, OR = 3,75 95% CI = 2,072– 6,788). In conclusion, while most participants were not at risk of MetS, central obesity emerged as a strong predictor. These findings underscore the need for early screening and intervention, even in physically active adolescents.